Determinants Of European Banks' Capital Adequacy - Klepczarek, Emilia (Comparative Economic Research. Central and Eastern Europe, 2015)
This paper examines the factors affecting the Common Equity Tier 1 Ratio (CET1), which is a measure of the relationship between core capital and the risk-weighted assets of banks. The research is based on a randomly selected sample from the group of banks examined by the European Central Bank authorities. The ECB conducted stress tests assessing the CET1 Ratio with respect to the Basel III regulations. The findings confirm the hypothesis about the impact of bank size and the risk indicators (risk-weight assets to total assets ratio and the share of loans in total assets) on banks’ capital adequacy. They also confirm strong effect of competitive pressure and the negative correlation between the CET1 Ratio and the share of deposits in non-equity liabilities, which may be explained by the existence of the deposit insurance system. Finally the paper presents the limitations of the study and conclusions regarding possible further research in this subject area.